Prevalence of acute mountain sickness among Finnish trekkers on Mount Kilimanjaro, Tanzania: An observational study - Karinen, H.; Peltonen, J.; Tikkanen, H. (High Altitude Medicine & Biology, 2008)
The aim of this study was to evaluate the prevalence of acute mountain sickness (AMS) among trekkers on Mount Kilimanjaro during the winter season of 2006-2007. A total of 130 Finnish trekkers at Marungu route were asked to complete daily a Lake Louise self-report and clinical assessment score questionnaire with the help of a trainee Finnish guide during their trek to Kilimanjaro. A Lake Louise questionnaire score = 3 indicated AMS. Altogether 112 mountaineers or travelers [54 men, 58 women, mean age 51 ± 10 (SD) years] were studied. Fifty-nine travelers (53%) reached Gillman's Point or Uhuru Peak. The incidence of AMS among Finnish Kilimanjaro trekkers was 75%. The most common high altitude symptoms were headache, followed by sleeping problems and fatigue or weakness. The incidence of AMS is high among trekkers climbing Mount Kilimanjaro.The main reason for this seems to be rapid ascent. Kilimanjaro treks normally have a fixed timetable, and for commercial reasons there is little opportunity to spend extra days for acclimatization in the camps. Some contributing factors are preventable, so we recommend an educational program for all the trekking agencies that guide on this peak and, in particular, the Tanzania-based guiding agencies, which, typically, are driving these very fast ascent rates.